The Relationship between Gender, Age, and Knowledge with Safety Riding Behaviour at Productive Age in Java Island - Puspoprodjo, Wishnu Uzma Aljauza; Laila, Nur Najmi (Universitas Muhammadiyah Surakarta, 2021)
According to World Health Organization (WHO) in the 2018 Global Status Report on Road, the number of deaths due to traffic accidents in the world increases to 1.35 million cases every year. In Indonesia, traffic accidents are also a serious problem and increasing every year. Therefore, this study aims to determine the relationship between gender, age, and knowledge with safety riding behaviour at productive age in Java. A descriptive study with a cross sectional study design was chosen to analyse. This research was conducted from March–October 2021. The population in this study were all users or riders of two–wheelers and four–wheelers of productive ages on Java Island. The research samples are 774 respondents with random sampling. Data were analysed using univariate analysis and bivariate analysis with chi-square test. The results of the study showed that the number of male respondents was 51.8%, age > 30 years was 53.1%, good knowledge was 54.4% and good safety riding behaviour was 63.7%. The results of statistical tests showed that there was a significant relationship between gender (OR 1.78 1.32-2.40), age (OR 1.72 1.28-2.32), knowledge (OR 2.59; 1.92- 3.50) with safety riding behaviour. It is recommended that the government and related parties provide more frequent socialization and education related to driving safety, especially for adolescents, young adult and women.